CORROSION OF GLASS FIBRES IN ULTRA HIGH PERFORMANCE CONCRETE AND NORMAL STRENGTH CONCRETE - Barbora Holubova; Helena Hradecka; Netusilova Marie; Gavenda Tadeas; Helebrant Ales (Ceramics-Silikáty, 2017)

(untitled)
Among other modern applications of glass fibres, there is a strong interest in their use as a strengthening agent for building materials. Alkali-Resistant (AR) glass fibres serving as ideal reinforcement for concrete proved to be very efficient against crack propagation at very early stages of the concrete setting process. However, a description of their behaviour in real cementous mixtures is missing because by now they have been studied mainly with various model tests simulating conditions of cementous environment. In this study two kinds of glass fibres (Anti-Crack HD and HP) were mixed into Normal Strength Concrete (NSC) and Ultra High Performance Concrete (UHPC) and stored under water for 28 days up to 1 year. Afterwards, chemical durability of the AR glass fibres was assessed mainly with SEM/EDS analysis. In general, the prepared samples did not demonstrate any signs of leaching or any other severe corrosion defects and they did not behave in a way suggested by the model tests, as reported in literature. In contrast to testing in high alkaline environment, no depleted corrosion layer rich in Zr and Ca was observed and functionality of the glass fibres remained unchanged.